Right ventricular dyssynchrony and its improvements after pulmonary rehabilitation in patients with chronic obstructive pulmonary disease - ÖZBEN SADIÇ, BESTE (WILEY, 2018)
PurposeWhether pathologic alterations of right ventricle (RV) in chronic obstructive pulmonary disease (COPD) affect intra- and interventricular dyssynchrony due to changes in mechanical activation of the septum and RV is unclear. The aim of this study was to determine mechanical activation and its changes after pulmonary rehabilitation program (PRP) with speckle tracking echocardiography (STE) in COPD patients. MethodsAfter the exclusion of 15 patients due to poor echogenicity and 5 patients not tolerating PRP out of 69 consecutive COPD patients undergoing PRP, the remaining 49 patients and 41 healthy subjects were enrolled. The mechanical activations of both ventricles were evaluated at admission and after PRP with STE. ResultsChronic obstructive pulmonary disease patients had intra- and interventricular dyssynchrony compared to controls. The interventricular dyssynchrony assessed by time to peak longitudinal systolic strain (PLSS) difference between RV free wall and left ventricle (LV) lateral wall and intraventricular dyssynchrony assessed by RV peak systolic strain dyssynchrony (PSSD) index were improved after PRP. In all, 18 patients were hospitalized due to symptoms of right heart failure within 1year. The time to PLSS difference between RV free wall and LV lateral wall and RV PSSD index were independent predictors of hospitalization. Receiver operating characteristics (ROC) analysis revealed that a time to PLSS difference between RV free wall and LV lateral wall >15ms predicted hospitalization within 1year with 77.8% sensitivity and 64.5% specificity. ConclusionsChronic obstructive pulmonary disease was associated with intra- and interventricular dyssynchrony. PRP had an important impact on the improvement of both intra-, and interventricular dyssynchrony, which might be used in predicting hospitalization within 1year.
Keywords: dyssynchrony; echocardiography; pulmonary rehabilitation; right ventricle; strain; EUROPEAN ASSOCIATION; AMERICAN SOCIETY; INTERVENTRICULAR DYSSYNCHRONY; ECHOCARDIOGRAPHIC-ASSESSMENT; RECOMMENDATIONS; STATEMENT; HEART; DYSFUNCTION; ACTIVATION; GUIDELINES